PENGEMBANGAN MODUL BERBASIS MULTIPEL REPRESENTASI SEBAGAI SUMBER BELAJAR PENDUKUNG PADA MATA KULIAH STOIKIOMETRI - Chusnur Rahmi (UIN AR-RANIRY, 2023)
This study is inspired by the lack of supporting learning tools in stoichiometry lectures, which causes students to struggle with the concept of the quantity of reactants and products involved in theoretical reactions and chemical calculations as a whole. To strengthen their comprehension of stoichiometric ideas at the macroscopic, submicroscopic, and symbolic levels, students require additional learning resources. The purpose of this research is to create modules based on numerous representations, exposing the amount of validity and practicability of modules as a source of student learning in stoichiometry courses. The research approach employed is R&D using the Dick & Carey development model through the steps of needs analysis, product design, validation, and evaluation. The study included two expert validators and 35 students from the Chemistry Education Study Program at UIN Ar-Raniry. Validity and practicality questionnaires were used to acquire research data. Based on the expert team's assessment, the learning module fulfilled the very valid criteria with an average assessment score of 95.17%. With a practicality score of 94.17% based on student responses, the learning module passes the criterion of being very practical. As a result, the multi-representation-based learning module may be inferred to be very valid and very practical for usage as a supporting learning resource for students in more optimal stoichiometry lectures.